Empreendedorismo internacional com características étnicas: uma análise sobre a inserção de steak houses de origem brasileira nos Estados Unidos - Teixeira, Elimar Kröner (Universidade do Vale do Rio dos Sinos, 2010)
The aim of this paper is to analyze the features of the insertion of steak houses of Brazilian origin in the United States. The analysis takes the viewpoint of international studies on entrepreneurship, especially those with ethnic characteristics, since they may account for the insertion of some international ventures. As a complement, it is considered the studies on the environment of experience that deal with the effects of environment during the interactive experiences of services. It is understood that such studies may also be explaining to the understanding of a sociocultural trend focused on the acceptance of products and services that provide a sense of cultural or ethnic identity. As a method of investigation, there will be an exploratory and descriptive case study of a steak house of Brazilian origin and which operates in the United States. Data analysis suggests that the internationalization of the steak house in focus, is associated with the entrepreneurial spirit of the founders and the use of resources acquired through experience combined with innovative service model. The analysis of the case does not reveal features recognized by the literature as prevalent in ethnic economies, ethnic and social networks, community networks and support in the insertion and maintenance of the enterprise. The data suggest that creating an environment that expresses a cultural tradition can be explanatory for the international integration of the company.
Keywords: Internacionalização; Empreendedorismo internacional; Empreendedorismo étnico e ambiente de experiência; Internationalization; International entrepreneurship; Ethnic entrepreneurship and environment of experience; ACCNPQ::Ciências Sociais Aplicadas::Administração